(untitled) (International Journal of Engineering and Computer Science, 2017)
Brakes has been an essential part of today’s modern automotive system. Brake are mechanical device that stops or retards the motion of moving member by absorbing kinetic energy and converting it heat energy. In the case of automobile this moving member is wheel. Brakes are not only important for stopping the vehicle but also for controlling it. Many different types of brakes are available in the market. Mostly disc brakes are preferred in two wheelers, because in disc brakes it gets enough time and space to disperse the heat produced during braking. Disc brake consists of brake pad, caliper, disc, hub and piston. Hub is attached to the wheels it rotates along with the wheels. Disc is attached to the hub and brake pad are mounted on disc on both side with the help of caliper. This caliper is operated by piston. When brakes are applied piston forces the caliper to move towards each other, thus forcing the brakes pads to rub against the rotating disc. And thus the speed of vehicle reduces and which eventually result in stopping of vehicle. In this paper we are modelling and analyzing the disc brake system of Honda CB Unicorn 150. Keywords: ANSYS, Disc Brake, Finite Element Analysis, SolidWorks, Honda